Safety and effectiveness of methylphenidate ER multi-unit pellet system in ADHD patients: An open label study - Renata Schoeman; Evelyn Y. Lai; Anne-Marie Nel; Mashra Gani; Muhammed A. Fulat; Akbar A. Mahomed (South African Journal of Psychiatry)
Background: Attention deficit hyperactive disorder (ADHD) is a neurodevelopmental disorder occurring in children and adults. Pharmacotherapy remains the cornerstone of ADHD treatment. Stimulants such as methylphenidate are effective and have been one of the best studied and most frequently used treatment for ADHD. However, different delivery mechanisms and devices may potentially impact patient experience and real-life outcomes.